Effect of the Tumor Suppressor miR-320a on Viability and Functionality of Human Osteosarcoma Cell Lines Compared to Primary Osteoblasts - Laura De-Ugarte; Susanna Balcells; Robert Guerri-Fernandez; Daniel Grinberg; Adolfo Diez-Perez; Xavier Nogues; Natalia Garcia-Giralt (Applied Sciences, 2020)
The miR-320a regulates a number of genes involved in various physiological processes. In particular, it has been reported as a tumor suppressor in several types of human cancers and involved in osteoporotic fracture and osteoblast function. Hence, the role of miR-320a has been evaluated in tumor cells and in primary cells in a separated context, but its effect has never been explored in a comparative manner. The present study aims to evaluate the cellular effects of miR-320a on human osteosarcoma cell lines (MG-63 and U2OS) compared to that on primary human osteoblasts (hOBs). miR-320a was either overexpressed or inhibited in all cell lines, and cell proliferation and viability were analyzed. Additionally, the effects of miR-320a on matrix mineralization, alkaline phosphatase activity, and oxidative stress were also evaluated in order to assess osteoblast functionality. In osteosarcoma cells, miR-320a overexpression reduced cell viability and proliferation, while in hOB cell viability was not affected and proliferation even was increased. The overexpression of miR-320a in both osteosarcoma cells and hOBs reduced the mineralization capacity. Finally, an increased oxidative stress was detected in all cells after miR-320a overexpression mainly in osteosarcoma. In conclusion, the overexpression of miR-320a increased stress oxidation levels, which could be involved in the reduced osteoblast performance, even though the cell viability was only affected in osteosarcoma cells.